Psychological Aspect: Relations Between Religious Attitude and Happiness in Youth Group - Karimov, Eldar (Scholarya Demo Journal of Ruby, 2020)
This article stuides one of the relevant issues of recent times in terms of relationship between religion and happiness in youth group. It discusses the psychological aspects of religious attitudes as well as the results of various studies on factors impacting the happiness. Simultaneously, the paper analyzes pictures of religious attitudes of different personality types and the feelings of happiness. The attention has been paid to differences of various happiness components individually and statements addressing these issues have been presented in the article. The article also analyzes the feelings, mindset and behavioral attitudes of youth that formulate their religious thinking to better understand its impact over their happiness. Considering the lack of local empirical studies on the subject, it studies the international literature aiming to contribute to future scientific research on this subject in Azerbaijan. The survey data has been collected from 516 different youth groups from different univesities of Azerbaijan. During the evaluation of the collected data t-test and one-way variance of analysis (ANOVA) were used. The study firstly examines the relationship between religion and happiness in terms of sex differences. Subsequently, religious attitudes and happiness of young people were assessed based on family income and health status that directly affected these feelings. As a result of our empirical evidence, we conclude that there is not any differences between the sexes in terms of religious attitudes and feelings of happiness, and differences in family income and health status.